On the Aerodynamic Forces on a Baseball, With Applications - Escalera Santos, Gerardo J.; Aguirre-López, Mario A.; Díaz-Hernández, Orlando; Hueyotl-Zahuantitla, Filiberto; Morales-Castillo, Javier; Almaguer, F-Javier (Frontiers in Applied Mathematics and Statistics, 2019)
The aerodynamic forces acting on a baseball are those produced by the contact between the ball and the air, and are defined by the initial conditions of the pitch. It is well known that such forces determine the changes from the typical parabolic ballistic trajectory, either in the direction of the movement of the ball (drag force), or producing a lift or lateral deflection (Magnus and seam forces). The drag and Magnus effects have been widely studied and there are many references about their nature and the trajectory they produce, which is predictable. This has led to most baseball research being related with spinning pitches. On the other hand, there is the unpredictable motion of a knuckleball, whose erratic trajectories and the poor understanding of the forces produced by the asymmetry of the seams had markedly limited the research about it until the beginning of this century. However, nowadays knuckleball's interest is resurfacing. Data collected by wind tunnel experiments and real pitches have motivated researchers to analyze the phenomenon and build models that try to predict the motion of the ball. In this work we aim to provide the reader some basic ideas on aerodynamic forces through a combination of experimental results, phenomenological and dimensional analysis, with special focus on new advances on the seam effects in knuckleball's pitches. In addition, we discuss the possible ways to extend the existing models about the seam forces. Finally, we sumarize from literature some methods regarding the reproduction and reconstruction of baseball trajectories from aerodynamic forces and discuss their application as well.